Граффито из «казармы» - Сапрыкин, С.Ю.; Дьячков, С.В. (My University, 1994)
Saprykin S. Yu., Dyachkov S. V. Graphittos from the "Barracks" In the course of excavations of large public building of Hellenistic time ("barrack"), situated near the town gate of antique Chersonesus, the stock of building ceramics of I–III A D. was revealed. On the tile fragment the graffito about the deal between Mides and Hilianos remained. If we suppose, that Mides was the owner of the building, we can obtain the interesting information about the functional purpose of "barrack" of Rome time and about the structure of its inhabitants.